2015
DOI: 10.1088/2040-8978/17/3/035604
|View full text |Cite
|
Sign up to set email alerts
|

Half Pearcey laser beams

Abstract: We obtain a new solution of the paraxial Helmholtz equation that describes a family of three-dimensional and two-dimensional form-invariant half-Pearcey beams (HP-beams). HP-beams generalize Pearcey beams obtained in Ring et al (2012) Opt. Express 20 18955, since these Pearcey beams can be considered as the sum of two first-order HP-beams. Three-dimensional HP-beams have angular spectra of plane waves, which are non-zero at a half parabola. For functions of HP-beam complex amplitudes, the orthogonality propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…where x ′ and y ′ are the transverse scaling factors of beams, w 0 denotes the Gaussian beam waist width. For the vth-order half-Pearcey beams, [15] when v=1, they can be defined as follows:…”
Section: Analytic Solution Of the Sdpgbs In The Free Spacementioning
confidence: 99%
See 2 more Smart Citations
“…where x ′ and y ′ are the transverse scaling factors of beams, w 0 denotes the Gaussian beam waist width. For the vth-order half-Pearcey beams, [15] when v=1, they can be defined as follows:…”
Section: Analytic Solution Of the Sdpgbs In The Free Spacementioning
confidence: 99%
“…The electric field of the symmetric dual Pearcey beams (SDPBs) in the initial plane is defined as: Ex0,y0,0=HPe+x0x,y0y+HPebadbreak−x0x,y0y\begin{equation} \begin{aligned} E{\left(x_0,y_0,0 \right)} &= \mathrm{HPe}^+{\left(\frac{x_0}{x^{\prime }},\frac{y_0}{y^{\prime }} \right)} +\mathrm{HPe}^-{\left(-\frac{x_0}{x^{\prime }},-\frac{y_0}{y^{\prime }} \right)} \end{aligned} \end{equation}where x$x^{\prime }$ and y$y^{\prime }$ are the transverse scaling factors of beams, w 0 denotes the Gaussian beam waist width. For the v th‐order half‐Pearcey beams, [ 15 ] when v =1, they can be defined as follows: HPe+X,Y=0+exp[]is4goodbreak+s2Y+sXnormalds\begin{equation} \begin{aligned} \mathrm{HPe}^+{\left(X,Y \right)} =\int _0^{+\infty }{\exp {\left[ \mathrm{i}{\left(s^4+s^2Y+sX \right)} \right]} \mathrm{d}s} \end{aligned} \end{equation} HPeX,Y=0exp[]is4goodbreak+s2Y+sXnormalds\begin{equation} \begin{aligned} \mathrm{HPe}^-{\left(X,Y \right)} =...…”
Section: Analytic Solution Of the Sdpgbs In The Free Spacementioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Ring et al theoretically confirmed that the Pearcey function is a particular solution of wave equation under paraxial approximation and successfully generated the Pearcey beams experimentally. [25] In 2014, a virtual source to generate Pearcey beams was demonstrated by Deng et al [26] In 2015, Kovalev et al [27] generated and introduced a family of form-invariant half-Pearcey beams (HP-beams). In 2016, it was reported that, based on the Fresnel diffraction catastrophes, dual Pearcey beams (DP beams) were successfully obtained by interfering a pair of half DP beams, [28] and the form-invariant Bessel beams were experimentally confirmed as particular forms of DP beams.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In Ref. [15] Pearcey beams were generalized into half Pearcey beams and it is shown that such beams, which are form-invariant, [12,15,16] propagate with acceleration and autofocusing.…”
Section: Introductionmentioning
confidence: 99%